The Role of Fatty Acid Synthase in the Vascular Smooth Muscle Cell to Foam Cell Transition - Bethany J Bogan; Holly C. Williams; Claire M Holden; Vraj Patel; Giji Joseph; Christopher Fierro; Hugo Sepúlveda; W. Robert Taylor; Amir Rezvan; Alejandra San Martín (2024)
Vascular smooth muscle cells (VSMCs), in their contractile and differentiated state, are fundamental for maintaining vascular function. Upon exposure to cholesterol (CHO), VSMCs undergo dedifferentiation, adopting characteristics of foam cells—lipid-laden, macrophage-like cells pivotal in atherosclerotic plaque formation. CHO uptake by VSMCs leads to two primary pathways: ABCA1-mediated efflux or storage in lipid droplets as cholesterol esters (CEs). CE formation, involving the condensation of free CHO and fatty acids, is catalyzed by sterol O-acyltransferase 1 (SOAT1). The necessary fatty acids are synthesized by the lipogenic enzyme fatty acid synthase (FASN), which we found to be upregulated in atherosclerotic human coronary arteries. This observation led us to hypothesize that FASN-mediated fatty acid biosynthesis is crucial in the transformation of VSMCs into foam cells. Our study reveals that CHO treatment upregulates FASN in human aortic SMCs, concurrent with increased expression of CD68 and upregulation of KLF4, markers associated with the foam cell transition. Crucially, downregulation of FASN inhibits the CHO-induced upregulation of CD68 and KLF4 in VSMCs. Additionally, FASN-deficient VSMCs exhibit hindered lipid accumulation and an impaired transition to the foam cell phenotype following CHO exposure, while the addition of the fatty acid palmitate, the main FASN product, exacerbates this transition. FASN-deficient cells also show decreased SOAT1 expression and elevated ABCA1. Notably, similar effects are observed in KLF4-deficient cells. Our findings demonstrate that FASN plays an essential role in the CHO-induced upregulation of KLF4 and the VSMC to foam cell transition and suggest that targeting FASN could be a novel therapeutic strategy to regulate VSMC phenotypic modulation.